AFFECT OF SALINITY ON SURVIVAL AND GROWTH OF TOMATO ANEMONEFISH (AMPHIPRION FRENATUS BREVOORT 1856) JUVENILES - Thuy, Nguyen Thi Thanh; Kien, Nguyen Trung (Vietnam Journal of Marine Science and Technology, 2008)
15 day old Tomato Anemonefish (Amphiprion frenatus Brevoorl 1856) were randomly divided info 8 treatments, reared in 2 liter glass bottles with 5 fish/liter in triplicates. Fish were separately tested for 15 days in different salinities such as. 0%o (de-chlorinated tape water), 5, 10, 15, 20, 30, 40%o and control (seawater: 34-35%o). The experiments were repeated twice in triplicates. The results showed that Tomato Anemonefish juveniles from 15 days old to one month old could be able to adapt and grow in salinities of 5 to 40%o. At salinity of 0%o the fish died totally after 15 h of testing. The survival of the fish after 15 days of testing in salinity of 5%o 1vas (74.17%) significantly lower than that of the control (95%) (ANOVA, p<0.05). The survival of the fish in salinities of 10, 15, 20, 30 and 40%o (75.50 to 88.35%) was not significant different (ANOVA, p>0.05) compared to those of the fish in the treatmems of 5%o (74.17%) and the control (95%). The growth rate in term of total length, height and weight of the fish in the treatments of 5, 10, 15, 20, 30 and 40%o was significantly lower than that of the fish in the control but not significant different among the treatments (ANOVA, p>0.05). However, the high standard deviations in survivals among the treatments of 5 to 20%o (SD: ± 12.96 to ± 18.86) approved vulnerable status of the fish in these salinities.